IMPORTANT PHYSICAL AND TECHNICAL MEANS OF HYDROGEN TRANSPORT - Temirov Og’abek Farhod o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Currently, the task of providing the energy supply of mankind through the achievements of science is one of the most urgent problems. One of the ways to solve this problem is the use of hydrogen energy. Hydrogen energy involves the use of hydrogen and/or hydrogen-containing compounds to produce energy for all practical purposes with high energy efficiency, environmental and social benefits, as well as economic competitiveness. In each period of the energy revolution, one can observe large innovative programs that had a great impact on human life. In the 21st century, humanity is at the beginning of a new energy frontier, and it can be overcome by the next series of undefined innovations. It is known from history that scientists are the main source of innovative ideas and revolutionary solutions in the field of energy. It is difficult to imagine future energy without alternative energy, and in this sense, the greatest hopes can be attributed to hydrogen energy.